Effect of annealing temperature on Cu2O thin films prepared by thermal oxidation method - Tran, Thi Ha (H. : ĐHQGHN, 2020)
We report a facile process to fabricate cuprous thin films by thermal oxidation of copper substrates. Structure and phase identification were studied by X-ray diffraction measurement and Raman spectroscopy. Scanning electron microscopy was utilized to study surface morphology of the as-fabricated thin films and optical properties of the samples were investigated by diffused reflectance spectroscopy. The study shows that cuprous thin films could be obtained by controlling annealing temperature in the region of 200-300 oC.